The Condition of the Working-Class in England in 1844 : with a Preface written in 1892 - Engels, Friedrich, 1820-1895; Kelley, Florence, 1859-1932 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Condition of the Working-Class in England in 1844" by Friedrich Engels is a study written in 1845. Based on Engels' observations during his time in Manchester and Salford, the book examines the lives of industrial workers in Victorian England. Engels argues that industrialization worsened workers' conditions, documenting higher mortality rates, lower wages, and unhealthy living environments in factory towns. This influential work helped convince Karl Marx that the working class could be agents of revolutionary change. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Condition_of_the_Working_Class_in_England
Release date is 2005-12-13
Transcribed from the January 1943 George Allen & Unwin reprint of the March 1892 edition by David Price
Keywords: Great Britain -- Economic conditions; Working class -- Great Britain